2016
DOI: 10.1159/000443086
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressive Role of MiRNA-509-5p by Targeting FOXM1 in Non-Small Cell Lung Cancer

Abstract: Background/Aims: Deregulation of microRNAs (miRNAs) expression is a frequent event in cancer development and progression. Recent studies have implied that abnormal expression of miRNAs is frequently observed in non-small cell lung cancer (NSCLC). Here, we examined the levels and biological functions of miR-509-5p in NSCLC. Methods: The levels of miR-509-5p were measured by real-time quantitative PCR (RT-PCR) in NSCLC cell lines and NSCLC tissues along with adjacent normal tissues. Cell viability was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…miRNA replacement therapy has shown some benefit in cancer treatment. The rationale for miRNA replacement therapy is that miRNAs play a causative role in tumourigenesis of cancer [22]. Due to the significant roles of miRNAs in cancer, they can function as either a tumour suppressor or an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA replacement therapy has shown some benefit in cancer treatment. The rationale for miRNA replacement therapy is that miRNAs play a causative role in tumourigenesis of cancer [22]. Due to the significant roles of miRNAs in cancer, they can function as either a tumour suppressor or an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that beneficial effects of crizotinib on ALK-positive NSCLC are elicited in combination with radiotherapy [28]. miRNAs play a critical role in the development of NSCLC and are considered as potential biomarkers for NSCLC diagnosis and therapy [29, 30]. Overexpression of miR-124, miR-148a, miR-3619-5p and miR-452 suppresses the growth, proliferation, metastasis and invasion of NSCLC cells [31-33].…”
Section: Discussionmentioning
confidence: 99%
“…To date, deregulated miRNAs and their roles in NSCLC development have attracted much attention. Some of them, including miR-21, miR-34a, miR-124, miR-148, miR-204, miR-221,miR-452, miR-497 and miR-509, et al, have been reported to participate in the initiation and progression of NSCLC and modulate the biological properties of cancer cells [12-25]. However, the role of miR-142-5p in NSCLC tumor development and metastasis has only recently been investigated and remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%